Genetic Deletion of 12/15 Lipoxygenase Promotes Effective Resolution of Inflammation Following Myocardial Infarction - Kain, Vasundhara (J Mol Cell Cardiol, 2018)
12/15 lipoxygenase (LOX) directs inflammation and lipid remodeling. However, the role of 12/15LOX in post-myocardial infarction (MI) left ventricular remodeling is unclear. To determine the role of 12/15LOX, 8-12 week-old C57BL/6J wild-type (WT; n=93) and 12/15LOX(−/−) (n=97) mice were subjected to permanent coronary artery ligation and monitored at day (d)1 and d5 post-operatively. Post-MI d28 survival was measured in male and female mice. No-MI surgery mice were maintained as d0 naïve controls. 12/15LOX(-/-) mice exhibited higher survival rates with lower cardiac rupture and improved LV function as compared with WT post-MI. Compared to WT, neutrophils and macrophages in 12/15LOX(-/-) mice were polarized towards N2 and M2 phenotypes, respectively, with increased of expression mrc-1, ym-1, and arg-1 post-MI. 12/15LOX(-/-) mice exhibited lower levels of pro-inflammatory 12-(S)-hydroperoxyeicosatetraenoic acid (12(S)-HETE) and higher CYP2J-derived epoxyeicosatrienoic acids (EETs) levels. CYP2J-derived 5,6-, 8,9-, 11,12-, and 14,15-EETs activated macrophage-specific hemeoxygenase (HO)-1 marked with increases in F4/80(+)/Ly6C(low) and F4/80(+)/CD206(high) cells at d5 post-MI in 12/15LOX(-/-) mice. In contrast, inhibition of HO-1 led to total mortality in 12/15LOX(-/-) mice by post-MI d5. 12/15LOX(-/-) mice exhibited reduced collagen density and lower α-smooth muscle actin (SMA) expression at d5 post-MI, indicating delayed or limited fibroblast-to-myofibroblast differentiation. In conclusion, genetic deletion of 12/15LOX reduces 12(S)-HETE and activates CYP2J-derived EETs to promote effective resolution of inflammation post-MI leading to reduced cardiac rupture, improved LV function, and better survival.